Mechanism of enhanced antiosteoporosis effect of circinal–icaritin by self-assembled nanomicelles in vivo with suet oil and sodium deoxycholate - Jiang J (Dove Medical Press, 2015)
Jun Jiang,1,2 Jie Li,1,2 Zhenhai Zhang,1,2 E Sun,1,2 Liang Feng,1,2 Xiaobin Jia1,21Key Laboratory of New Drug Delivery System of Chinese Materia Medica, Jiangsu Provincial Academy of Chinese Medicine, 2College of Pharmacy, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of ChinaBackground: Circinal–icaritin (CIT), one new active aglycone of Epimedium, can exert a beneficial effect on osteoporotic bone. However, its low bioavailability limits its clinical efficacy for the treatment of osteoporosis.Materials and methods: In this paper, suet oil (SO) was used to improve the oral bioavailability of CIT and enhance its antiosteoporosis effect and absorption. After oral administration of CIT together with SO, the CIT and SO self-assembled into nanomicelles under the action of sodium deoxycholate (DOC) by bile secretion. The antiosteoporosis effects of the CIT-SO-DOC nanomicelles were evaluated in osteoporotic rats by bone mineral density, serum biochemical markers, bone microarchitecture, bone biomechanical properties, and related protein and gene expressions. We examined the bioavailability of CIT and its nanomicelles in vivo, and subsequently the nanomicelles were verified using transmission electron microscopy. Finally, we evaluated absorption across a rat intestinal perfusion model.Results: Compared with CIT, in the CIT-SO groups, protein and messenger ribonucleic acid expressions of osteoprotegerin were increased, while expressions of receptor activator of nuclear factor-κB ligand in bone tissue were decreased; bone-turnover markers in serum of hydroxyproline, alkaline phosphatase, tartrate-resistant acid phosphatase 5b, and receptor activator of nuclear factor-κB ligand levels were decreased, while osteoprotegerin and osteocalcin levels were increased; and trabecular bone mass, microarchitecture, and bone biomechanical strength were enhanced. The relative bioavailabilities of CIT-SO high dosage, CIT-SO medium dosage, and CIT-SO low dosage (area under concentration–time curve [AUC]0–∞) compared with that of raw CIT high dosage, CIT medium dosage, and CIT low dosage (AUC0–∞) were 127%, 121%, and 134%, respectively. The average particle size of CIT-DOC was significantly decreased after adding SO (P<0.01), and the intestinal permeability coefficients of CIT-SO-DOC nanomicelles in the duodenum, jejunum, ileum, and colon were all significantly improved (P<0.01).Conclusion: The increased antiosteoporosis effects and bioavailability of CIT-SO-DOC self-assembled nanomicelles were due to an increase in absorption of CIT by reducing the particle sizes of CIT. SO may be a practical oral carrier for antiosteoporosis drugs with low bioavailability.Keywords: circinal–icaritin (CIT), nanomicelles, antiosteoporosis effect, bioavailability, intestinal absorption